2015
DOI: 10.1007/s00253-015-6835-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nitrogen sources on growth and fermentation performance of different wine yeast species during alcoholic fermentation

Abstract: In this study, the influence of twenty different single (i.e. 19 amino acids and ammonium sulphate) and two multiple nitrogen sources (N-sources) on growth and fermentation (i.e. glucose consumption and ethanol production) performance of Saccharomyces cerevisiae and of four wine-related non-Saccharomyces yeast species (Lachancea thermotolerans, Metschnikowia pulcherrima, Hanseniaspora uvarum and Torulaspora delbrueckii) was investigated during alcoholic fermentation. Briefly, the N-sources with beneficial effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
86
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(108 citation statements)
references
References 48 publications
19
86
2
1
Order By: Relevance
“…The production of lactic acid during fermentations with variable glucose contents in model media (8,12, 16% w/w) is stable and independent of sugar levels, ranging from 2.48 ± 0.8-2.66 ± 0.9 g/L for LT strain L3.1 [41]. However, when the same sugar concentrations were tested in the presence of 2 g/L of lactic acid, the production by LT was affected, ranging from 1.25 ± 0.7 g/L (in model media with 8% w/w glucose) to 3.68 ± 0.3 g/L (with 16% w/w glucose).…”
Section: Biotechnological Application: Wine Acidificationmentioning
confidence: 99%
See 1 more Smart Citation
“…The production of lactic acid during fermentations with variable glucose contents in model media (8,12, 16% w/w) is stable and independent of sugar levels, ranging from 2.48 ± 0.8-2.66 ± 0.9 g/L for LT strain L3.1 [41]. However, when the same sugar concentrations were tested in the presence of 2 g/L of lactic acid, the production by LT was affected, ranging from 1.25 ± 0.7 g/L (in model media with 8% w/w glucose) to 3.68 ± 0.3 g/L (with 16% w/w glucose).…”
Section: Biotechnological Application: Wine Acidificationmentioning
confidence: 99%
“…Also, an improvement in the production of 2-phenylethanol and glycerol has been described.Fermentation 2018, 4, 53 2 of 12 necessary a minimum of 200 mg/L of YAN (yeast assimilable nitrogen) to avoid sluggish or stuck fermentations [7]. Serine as N-source also has shown an improvement in the fermentation performance of LT [8]. Strains of LT can express the following extracellular enzymatic activities with effect in wine aroma or phenol extraction: Esterase, Esterase-Lipase, ß-glucosidase, Pectinase, Cellulase, Xylanase, Glucanase [9].Fermentation 2018, 4, x 2 of 12 LT is able to ferment glucose and sucrose [5] and weakly galactose.…”
mentioning
confidence: 99%
“…Supplementation of N using ammonium salts (sulfate or phosphate) encourages a higher growth rate and biomass yield and also stimulates fermentation activity (Jiranek et al 1995, Kemsawasd et al 2015. Nitrogen deficiency directly restricts growth and metabolic activity during this process, so external supplementation should be used to achieve an adequate fermentation rate.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen deficiency directly restricts growth and metabolic activity during this process, so external supplementation should be used to achieve an adequate fermentation rate. Supplementation of N using ammonium salts (sulfate or phosphate) encourages a higher growth rate and biomass yield and also stimulates fermentation activity (Jiranek et al 1995, Kemsawasd et al 2015. The addition of up to 1 g/L diammonium phosphate (DAP) is allowed under Annex IV to European Regulation 1493/1999(European Commission 1999.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that yeasts produce higher concentrations of SO 2 under higher yeast assimilable nitrogen (YAN) quantities [7,29]. The supplementation on nitrogen using ammonium salts (sulfate or phosphate) allows higher growth rates and biomass yielding and also the stimulation of the fermentative activity [30,31]. The addition of diammonium phosphate (DAP) significantly decreases H 2 S production and improves the kinetics of fermentation and aroma profile of wine [32].…”
Section: Microbiological Strategies To Elaborate So 2 -Free Winesmentioning
confidence: 99%